Does labour migration necessarily promote farmers' land transfer-in?—Empirical evidence from China's rural panel data. (January 2023) - Huang, Kai; Cao, Sha; Qing, Chen; Xu, Dingde; Liu, Shaoquan
Abstract: With rapidly advancing urbanization and agricultural modernisation in China, some of the rural labour force has transferred to urban non-agricultural sectors for employment, resulting in the transformation of rural land-use patterns. Based on data from the China Labour-Force Dynamics Surveys from 2012, 2014, 2016 and 2018, IV-Probit and IV-Tobit models were constructed to determine the impact of labour migration (off-farm employment and part-time employment) on land transfer-in (whether farmers opt for land transfer-in and the scale of land transfer-in). The results were as follows. (1) Off-farm employment had a significant negative impact on the occurrence and area of farmers' land transfer-in; the inhibitory effect of off-farm employment on whether farmers had land transfer-in and the area of land transfer-in by farmers generally increased. The impact of part-time employment on the occurrence and area of farmers' land transfer-in was negative but this effect was not significant in 2012 and 2014. (2) Mediation analyses showed that off-farm employment could suppress land transfer-in either by increasing per capita income or by improving employment stability; both of these were partial mediating effects. Part-time employment reduced the probability of farmers opting for land transfer-in by increasing per capita income and improving the stability of off-farm jobs but only in 2016 and 2018. (3) Heterogeneity analysis showed that the impacts of off-farm and part-time employment on farmers' land transfer-in in suburbs were greater than for non-suburban farmers. Additionally, the inhibition effect of rural off-farm employment on land transfer-in in mountainous areas was greater than on the plains and in hilly areas. Highlights: Labor migration will restrain rural households from choosing land transfer-in. Labor migration mainly affects the rural households' land transfer-in through two paths involving household income and stability of off-farm jobs. The impact of labor migration on farmers' land transfer-in in suburbs were greater than for non-suburban farmers. Additionally, the inhibition effect of rural off-farm employment on land transfer-in in mountainous areas was greater than that on plains and in hilly areas.